Simplified approach for generating integrity tests in distributed database systems. (1st January 2013) - Hanandeh, Feras; Abdallah, Emad E.; Abdallah, Alaa E.; Al-Daoud, Essam
Distributed database systems (DDBS) usually contain massive collections of data that rapidly evolve over time. It is extremely time consuming to make a perfect checking at each database update operation. This paper introduces a new algorithm to generate simplified integrity tests which could be used to automatically verify that database updates does not introduce any violation of integrity. The main attractive features of this approach are simplicity, flexibility in generating sufficient and complete integrity tests, and considering all conjunctive and disjunctive constraints. The experiment results show that the new algorithm provides more tests in comparison with existing techniques.